Use of Etomidate for Rapid Sequence Intubation (RSI) in Pediatric Trauma Patients: An Exploratory National Survey - Jeffrey J. Cies; Matthew L. Moront; Wayne S. Moore II; Renata Ostrowicki; Kelsey B. Gannon; Shonola S. Da-Silva; Arun Chopra; Jason Parker (MDPI AG, 2015)
Objective, To survey the pediatric trauma programs to ascertain if and how etomidate is being used for rapid sequence intubation (RSI) in pediatric trauma patients. Design, A 25 question survey was created using REDCaps.  A link to the survey was emailed to each of the pediatric and adult trauma programs that care for pediatric patients. Setting, Pediatric trauma programs and adult trauma programs caring for pediatric patients. Intervention, None. Measurements and Main Results, A total of 16% of programs responded (40/247). The majority of the centers that responded are urban, academic, teaching Level 1 pediatric trauma centers that provide care for > 200 pediatric trauma patients annually.  The trauma program directors were the most likely to respond to the survey (18/40).  33/38 respondents state they use etomidate in their RSI protocol but it is not used in all pediatric trauma patients.  26/38 respondents believe that etomidate is associated with adrenal suppression and 24/37 believe it exacerbates adrenal suppression in pediatric trauma patients yet 28 of 37 respondents do not believe it is clinically relevant. Conclusions, Based on the results of the survey, the use of etomidate in pediatric trauma patients is common among urban, academic, teaching, level 1 pediatric trauma centers.  A prospective evaluation of etomidate use for RSI in pediatric trauma patients to evaluate is potential effects on adrenal suppression and hemodynamics is warranted.